PENGARUH PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI (KASUS KARYAWAN PT. PANIN BANK KANTOR CABANG PEKANBARU - Devia Armawati; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Career development is a process to improve the skills of the individual inorder to get a better career. And organizational commitment reflects the extent towhich an individual knows and tied to the organization. The aim of this study wasto understand the career development, organizational commitment and careerdevelopment to test the influence of organizational commitment of employees ofPT. Panin Bank Kantor Cabang Pekanbaru.The method used in this research is descriptive and analytical techniquesused is quantitative analysis. The sampling technique used was purposivesampling with a population of 67 people and a sample of 40 respondents. Datameasured using Likert Scale. And then the data is processed by using SPSS 17..The results showed that the influence of career development by PT. PaninBank Kantor cabang pekanbaru organizational commitment showed a quite wellcriteria and appropriate.Keywords: Career Development, Organizational commitment, PT. Panin BankKantor Cabang Pekanbaru